Predicting Entrepreneurial and Crowdfunding Intentions ‒ A Study of Romania and South Korea - Mina Fanea-Ivanovici; Hasnan Baber (Amfiteatru Economic)
Crowdfunding has recently gained ground as an alternative financing means, particularly for start-ups and risky enterprises. We hereby analyse Romanian and South Korean students’ intentions to use crowdfunding in their future ventures. Using PLS-SEM (N=441), we first investigated the influence of the Theory of Planned Behaviour variables- attitudes, social norms, perceived behavioural control along with entrepreneurship education on entrepreneurial intentions. In addition, we looked into the influence of perceived trust and risk, performance expectancy, effort expectancy and facilitating conditions on crowdfunding intentions. Finally, we checked entrepreneurial intentions with crowdfunding intentions. We find that attitudes towards entrepreneurship, social norms, and entrepreneurial education have a positive influence and perceived behavioural control have a negative influence on entrepreneurial intentions. In terms of crowdfunding intentions, they were found to be positively influenced by performance expectancy, perceived trust and risk and entrepreneurial intentions. The results are useful both for educators designing higher education programmes in the field of entrepreneurship, as well as for crowdfunding platform owners in designing platform functionalities and image.